MRI contrast agents and retention in the brain: review of contemporary knowledge and recommendations to the future - Vymazal, Josef; Rulseh, Aaron M (Insights into imaging, 2024)
Gadolinium-based contrast agents (GBCA) were introduced with high expectations for favorable efficacy, low nephrotoxicity, and minimal allergic-like reactions. Nephrogenic systemic fibrosis and proven gadolinium retention in the body including the brain has led to the restriction of linear GBCAs and a more prudent approach regarding GBCA indication and dosing. In this review, we present the chemical, physical, and clinical aspects of this topic and aim to provide an equanimous and comprehensive summary of contemporary knowledge with a perspective of the future. In the first part of the review, we present various elements and compounds that may serve as MRI contrast agents. Several GBCAs are further discussed with consideration of their relaxivity, chelate structure, and stability. Gadolinium retention in the brain is explored including correlation with the presence of metalloprotein ferritin in the same regions where visible hyperintensity on unenhanced T1-weighted imaging occurs. Proven interaction between ferritin and gadolinium released from GBCAs is introduced and discussed, as well as the interaction of other elements with ferritin; and manganese in patients with impaired liver function or calcium in Fahr disease. We further present the concept that only high-molecular-weight forms of gadolinium can likely visibly change signal intensity on unenhanced T1-weighted imaging. Clinical data are also presented with respect to potential neurological manifestations originating from the deep-brain nuclei. Finally, new contrast agents with relatively high relaxivity and stability are introduced. CRITICAL RELEVANCE STATEMENT: GBCA may accumulate in the brain, especially in ferritin-rich areas; however, no adverse neurological manifestations have been detected in relation to gadolinium retention. KEY POINTS: Gadolinium currently serves as the basis for MRI contrast agents used clinically. No adverse neurological manifestations have been detected in relation to gadolinium retention. Future contrast agents must advance chelate stability and relativity, facilitating lower doses.